2014
DOI: 10.2478/s11696-013-0471-0
|View full text |Cite
|
Sign up to set email alerts
|

Determination of mercury species using thermal desorption analysis in AAS

Abstract: Analytical aspects of the determination of inorganic mercury (Hg) species by thermal desorption followed by atomic absorption spectrometry (AAS) detection were investigated in this work. Characteristic Hg release curves of the following species were observed: Hg0, HgCl2, HgO, HgSO4, HgS, and the Hg bound to humic acids. Particular attention was dedicated to the thermal stability and change of bond of Hg0 in the following matrices: sand, kaolinite, granite, peat, power plant ash, and soil. The bond of elemental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Although, experimentally defined temperature of HgS thermal desorption is 365 °C (range between 250 -435 °C) 36 here, nano size HgS particles were used. It is expected that volatility of nano size HgS will differ from the commercially available bulk material.…”
Section: Hg Species Quantification By Species Specific Isotope Dilutimentioning
confidence: 99%
“…Although, experimentally defined temperature of HgS thermal desorption is 365 °C (range between 250 -435 °C) 36 here, nano size HgS particles were used. It is expected that volatility of nano size HgS will differ from the commercially available bulk material.…”
Section: Hg Species Quantification By Species Specific Isotope Dilutimentioning
confidence: 99%
“…It is believed that the intermediate peak in our case may have represented the Small Hg peaks could also be observed in the temperature range between 200 and 470°C. Although one step decomposition was suggested by some authors, it seems more likely that HgSO 4 decomposes through several stages [11,15,20,31] (Eqs. 9 and 10).…”
Section: Hg 2 Somentioning
confidence: 99%
“…Some methods involving different approaches have been tested by Biester and Scholz [4], Shuvaeva et al [12], Lopez-Anton et al [13], Rallo et al [14], Luo et al [15], Bollen et al [16], Iwashita et al [17], Wu et al [18], Coufalik et al [19,20] etc. However, no procedure for temperature fractionation of Hg has been validated or standardized yet, and therefore its comparability is questionable due to procedural differences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Different Hg detoxification studies have shown the efficient quantification of non-radioactive volatilization of mercury using CV-AAS [25,26].…”
mentioning
confidence: 99%